Influence of age and body mass index on arterial stiffness and left ventricular hypertrophy in patients with arterial hypertension II stage. - Kolesnyk, T. V.; Nadiuk, A. V.; Kosova, H. A. (Medicni Perspektivi, 2019)
Based on the cumulative data of scientific research reference values for the central blood pressure and its amplification were proposed in patients with different cardiovascular risk factors. Still, the possibility of its practical implementation in patients of different age groups has not been fully studied. There were examined 132 untreated patients (23 females and 109 males) with uncomplicated essential hypertension, which were divided into 3 groups depending on age (WHO, 2012): I group included 47 patients of the young age, II group - 50 middle-aged patients and III group – 35 elderly patients. Measurements of central systolic blood pressure (cSBP), SBP amplification (SBP Amp), pulse wave velocity (PWV) were carried out by Arteriograph Tensioclinic (Tensiomed, Hungary). Target-organ damage included LVH which was determined by echocardiographic left ventricular mass index (LVMI), adjusted for body surface (g/m2) or height (LVMI2,7), aortic PWV>10 m/s. It was established that the use of a personalized approach in the examination of patients with arterial hypertension makes it possible to increase the efficiency of diagnosis of hypertensive-mediated subclinical organ damage. So in order to identify impairment of the vascular wall in patients of a young age with hypertension, with overweight and obesity, the reference values of PWV and cSBP in accordance with the age norm should be taken into account. It was particularly in this cohort of patients that the greatest adverse effect of vascular stiffness and body mass index (BMI) on the formation of left ventricular hypertrophy was revealed, while in elderly people it is necessary to use the reference values of cSBP, depending on the degree of hypertension.